(3CShGb GdCThGb ef eUGQY GdYTGbs - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s ((3Ydi Hf eMeO GdefXQGhi s)
(3ChdgG (B:s
(3bGd GdTjN GdHbGYi CeG HYO aEf cJGH eUGQY GdYTGb dGHi eMeO LYaQ Hf CMeO GdSQGL fRd ef CfS GdbdhH GdbQjMI efRdI Gdaf ef GdeMJGL s
(3BNQgG (B:s
(3HJeOjf dGMJ fGQ djdi hUMHJi HaQZ GdZVG JRLi GdbdGMG GdMhGejG gPG eG CQOJ EKHGJg MSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs